2016
DOI: 10.1007/s00296-016-3622-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of arthritis and vitamin D insufficiency with physical disability in Mexican older adults: findings from the Mexican Health and Aging Study

Abstract: Objective Arthritis and vitamin D insufficiency are prevalent in older adults and are risk factors for disability. The objective of this study was to examine the effect of co-ocurring arthritis and vitamin D defficiency on upper-lower extremity functional limitations and disability in older adults. Methods We examined 1,533 participants aged ≥50 years from a subsample of the Mexican Health and Aging Study. Measures included sociodemographics, body mass index, comorbid conditions, falls, physical activity, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…Any ADL disability was dichotomized as having difficulty in or not performing one or more of the six ADLs. These questions have been used in previous studies [25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…Any ADL disability was dichotomized as having difficulty in or not performing one or more of the six ADLs. These questions have been used in previous studies [25,26]. …”
Section: Methodsmentioning
confidence: 99%
“…5 Not surprisingly, studies have shown an association between low vitamin D status and musculoskeletal disorders. [6][7][8] The objective of the present study was to assess serum levels of vitamin D, parathyroid hormone, calcitonin, calcium, phosphorus and magnesium in patients with TMDs versus patients without TMDs. To the best of the authors' knowledge, the present report is the first published investigation of vitamin D levels and associated parameters in patients with TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of an association between 25(OH)D concentration and disability trajectories in our study is inconsistent with the findings of prospective cohort studies that investigate the association between vitamin D status and disability in those age 65 years and over. For example, two studies found that a 25(OH)D < 50 nmol/L increased the risk of disability in arthritis and multiple sclerosis patients, respectively [11,12]. Likewise, Semba, et al [13] found that a 25(OH)D < 50 nmol/L was associated with a higher possibility of disability in women aged over 65 years and living in the community.…”
Section: Evidence From Other Studiesmentioning
confidence: 99%
“…Maintaining adequate concentrations of 25(OH)D may protect against disability in terms of both musculoskeletal and cognitive function; the few studies that have assessed this association have found inverse associations between 25(OH)D concentration and risk of disability [8,[11][12][13]. However, these studies have several limitations including: use of different definitions of low 25(OH)D concentration; being cross-sectional rather than longitudinal; recruited those aged 65 and over with few studies of the very old; being unrepresentative because they recruited women only [8,13], targeted at a specific ethnic group [12] or involved patients with a specific disease [11]. Consequently there is a need for longitudinal studies of associations between 25(OH)D concentration and disability trajectory and which focus on very-old adults, including those living in institutions.…”
Section: Introductionmentioning
confidence: 99%